Description of Instructor Professional Competence in English Language Courses at the BEC Educational Institution in Sawahlunto - Winda Maiyastri; Solfema Solfema; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
This study is based on the effectiveness of learning outcomes pf high learning citizens, motivation and high learning activeness. This condition is suspected because of the excellent professional competence of the instructor. The purpose of the study is to see the competence of the instructor in 1) planning the lesson, 2) carrying out the learning, 3) evaluating the learning, 4) developing the learning of the English course. The population is forty-six people and the sample is forty-six people determined based on sampling technique that is the sensus method. Data collection techniques used questionnaire data collection tool-using questionnaires. Data analysis techniques use percentage calculations. The results showed that the professional competence of the instructor was very good seen from 1) planning the learning, 2) implementing the learning 3) evaluating the learning, 4) developing the learning. Conclusion instructors have excellent professional competence. The professional competence of this instructor will influence the improvement of the learning outcomes of the learners.Keywords: Competence, Professional Instructor